The analysis of the dynamics of psychiatrists ‘ opinions on continuing medical education - N. N. Petrova; I. A. Fedotov; E. M. Chumakov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
To assess the dynamics of doctors ‘ opinions on continuing medical education (CME) in 2016 and 2018 was conducted an anonymous online survey, which was attended by 52 psychiatrists (in 2016 year, from 14 regions of Russia) and 203 psychiatrists (in 2018 year, from 46 regions of Russia). There is the growth of skeptical views on the feasibility of introducing a new system (in 2016 it was supported by 55,8% of respondents, in 2018 — only by 38,3%). Also in the 2-year term increased the number of difficulties in accessing to attend conferences, increased availability of online modules and has not changed significantly the availability of training in the departments in universities. The most difficult for doctors is to find attending conferences (average score in assessing difficulties 3,6), which requires the search for funds for travel expenses and separation from work, the most convenient — online training (average score in assessing difficulties 3,0). The effectiveness of all three types of educational activities of CME (conferences, online modules and courses in the departments) is estimated at a relative average level (about 3 points on a 5-point scale). The impact of CME on the solution of actual organizational and methodological problems of health care is also rather skeptical.